EFEKTIVITAS PELAYANAN IZIN BERUSAHA BERBASIS ONLINE SINGLE SUBMISSION - Muhamad Tengku; Rita Rahmawati; Irma Purnamasari; Euis Salbiah (Universitas Djuanda Bogor, 2023)
The main objective of the online application-based business permit (OSS) service is to speed up the issuance of permits, including business permits, especially through the application of digitalization, reducing bureaucrats' time and efficiency, as well as increasing business in the Bogor city environment. However, the system (server) is still experiencing problems, frequently crashing and making the OSS portal page difficult to access. This failure occurred because many people accessed the OSS website at the same time, making it difficult to access the OSS website. It turns out that OSS sites are somewhat limited when migrating a system. This means that the availability of the OSS system is not sufficient due to the availability of information and system updates. The aim of this research is to evaluate the effectiveness of online simple submission (OSS) based business approval services in integrated capital investment and integrated services. This research examines the effectiveness of OSS-based licensing services through quantitative descriptive methods and data analysis using the Weight Mean Score (WMS) and Richard M. Strayer's theory, as well as examining aspects of goal achievement, adaptation and completion. The aim is to explain the method. The results show that the online application licensing service (OSS) speeds up the business licensing process, reduces bureaucratic time, makes it easier for businesses to obtain approval, and improves the growing business and venture investment ecosystem in an organized and accountable manner.